العلاقة بين مكونات الحرية الاقتصادية والحريات السياسية دراسة قياسية على عينة من دول MENA - صيوح لؤي; محمود ريم (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This study aimed to test the relationship between the components of economic freedom and political freedoms in (6) Arab countries of the (MENA) Group during the period 2006-2015, based firstly on studying and reviewing the intellectual trends and the empirical studies on this relationship. and secondly on a Econometric study based on (Panel Data), and an estimation of the parameters of the model after the tests of data stability using the (FEM) model which was chosen according to the (F-Statistique) value of the (Wald) test. The results of the standard study showed that the associated variables (property rights, financial freedom , investment freedom) and the rate of change in the level of monetary freedom (differential value) have a significant positive impact on the level of political freedoms . In other hand the study showed a significant negative impact of the rate of change in the level of government intervention on political freedoms in the sample countries studied, which is consistent with economic theories. The results of the (Kao) test showed a common correlation between the studied variables, which allowed the (Granger Causality Test) to test the causal relationship between the dependent variable and the independent variables. The results of the test showed no two-way causal relationship between the variables, but showed a one-way causal relationship between the financial freedom variable, government intervention towards the political freedoms variable, and a one-way causal relationship from the political freedoms variable to the property rights variable. Due to the importance of the relationship between the components of economic and political freedoms, and its impact on the lives of individuals economically and politically, and according to the lack of studies that dealt with that in the Arab countries, the study recommends further studies on the nature of this relationship and the factors affecting it. هدفت هذه الدراسة إلى اختبار العلاقة بين مكونات الحرية الاقتصادية والحريات السياسية في (6) دول عربية من مجموعة(MENA) خلال الفترة (2006ــــ2015)، وذلك بالاعتماد أولاً على دراسة واستعراض التيارات الفكرية والدراسات التجريبية التي تناولت العلاقة الارتباطية فيما بينهما، وثانياً على دراسة قياسية ترتكز على بيانات (Panel Data)، وتقوم على تقدير معلمات النموذج ــ بعد إجراء اختبارات الاستقرارية والسكون لهذه البيانات ــ وفق نموذج الآثار الثابتة (FEM) الذي تم اختياره بالاعتماد على القيمة الاحتمالية لــ (F-Statistique) لاختبار (Wald). أظهرت نتائج الدراسة القياسية أن المتغيرات المرتبطة ( بحقوق الملكية، التحرر المالي، حرية الاستثمار)، إضافة إلى معدل التغير في مستوى الحرية النقدية (القيمة التفاضلية) أثر ايجابي ومعنوي في مستوى الحريات السياسية. بينما أظهرت الدراسة وجود أثر سلبي ومعنوي لمعدل التغير في مستوى التدخل الحكومي في الحريات السياسية في بلدان العينة المدروسة وهو ما يتوافق مع النظريات الاقتصادية. كذلك أظهرت نتائج اختبار(Kao) وجود علاقة تكامل مشترك بين المتغيرات المدروسة، مما سمح بتطبيق سببية Granger (Granger CausalityTest) لاختبار وجود علاقة سببية بين المتغير التابع والمتغيرات المستقلة المعنوية. أظهرت نتائج الاختبار عدم وجود علاقة سببية ثنائية الاتجاه بين المتغيرات، ولكنها أظهرت وجود علاقة سببية أحادية الاتجاه بين كل من متغير التحرر المالي، التدخل الحكومي باتجاه متغير الحرية السياسية، وعلاقة سببية أخرى أحادية الاتجاه من متغير الحرية السياسية إلى متغير حقوق الملكية. نظراً لأهمية العلاقة بين مكونات الحرية الاقتصادية والحريات السياسية، وأثرها في حياة الأفراد اقتصادياً وسياسياً، وقلة الدراسات التي تناولتها على مستوى الدول العربية، توصي الدراسة بإجراء المزيد من الدراسات حول طبيعة هذه العلاقة و العوامل المؤثرة بها.